Synergistic effects of alkali content and silicate modulus optimization for enhanced properties in alkali-activated ultra-high performance concrete at ambient and high temperature - Yunfeng Qian; Dingyi Yang; Yunxiao Yan; Guosheng Ren; Miao Liu (Case Studies in Construction Materials)
This study comprehensively examines the combined effects of alkali content and silicate modulus on the mechanical properties, moisture transport behavior, and microstructural evolution of alkali-activated ultra-high performance concrete (A-UHPC) under both ambient and elevated temperatures. Unlike previous studies that focused separately on ambient or high-temperature performance, this research offers a holistic evaluation of the manner in which these parameters influence A-UHPC across varying thermal conditions. Experimental evaluations, including mechanical strength tests, moisture transport analysis, and microstructural characterization (SEM, TGA, XRD, FTIR), demonstrate that the optimal synergy of 6 % alkali content and a 1.6 M silicate modulus results in superior compressive strength (132.60 MPa), reduced porosity, and enhanced durability. At elevated temperatures, this formulation retains structural integrity up to 400℃ but experiences substantial deterioration at 800℃ due to phase transformations and microstructural degradation. These findings contribute critical insights for optimizing A-UHPC to achieve enhanced mechanical performance and fire resistance, laying a foundation for its broader application in extreme environments.